2014
DOI: 10.1371/journal.pone.0108868
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of the nos-pdt Operon to Virulence Phenotypes in Methicillin-Sensitive Staphylococcus aureus

Abstract: Nitric oxide (NO) is emerging as an important regulator of bacterial stress resistance, biofilm development, and virulence. One potential source of endogenous NO production in the pathogen Staphylococcus aureus is its NO-synthase (saNOS) enzyme, encoded by the nos gene. Although a role for saNOS in oxidative stress resistance, antibiotic resistance, and virulence has been recently-described, insights into the regulation of nos expression and saNOS enzyme activity remain elusive. To this end, transcriptional an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
58
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(63 citation statements)
references
References 70 publications
5
58
0
Order By: Relevance
“…The S. xylosus C2a Δ nos mutant displayed higher colony pigmentation than the wild-type strain after prolonged cultivation on agar medium, as observed for the S. aureus Δ nos strain UAMS-1 (Sapp et al, 2014). S. aureus produced the intermediary yellow carotenoid 4,4′-diaponeurosporene, which, after prolonged cultivation, is converted to the yellow-orange end-product staphyloxanthin (Wieland et al, 1994).…”
Section: Discussionmentioning
confidence: 59%
See 4 more Smart Citations
“…The S. xylosus C2a Δ nos mutant displayed higher colony pigmentation than the wild-type strain after prolonged cultivation on agar medium, as observed for the S. aureus Δ nos strain UAMS-1 (Sapp et al, 2014). S. aureus produced the intermediary yellow carotenoid 4,4′-diaponeurosporene, which, after prolonged cultivation, is converted to the yellow-orange end-product staphyloxanthin (Wieland et al, 1994).…”
Section: Discussionmentioning
confidence: 59%
“…The Δ nos mutant was unable to produce NO under aerobic conditions. The loss of NOS activity in S. aureus UAMS-1 mutant led to NO production of 65% as evaluated using fluorescent stain DAF-FM diacetate after growth on agar plates (Sapp et al, 2014), while the deletion of nos in S. aureus UAMS1182 completely abolished NO production after growth under aerobic conditions (van Sorge et al, 2013). These results revealed that some Staphylococcus strains are able to produce NO by other pathways under limited oxygenation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations